2018
DOI: 10.1111/jonm.12718
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and health‐promoting self‐care: Do we practice what we preach?

Abstract: Nurse managers should practice self-care by engaging in exercise, proper nutrition and demonstrating work-life balance, both to protect their own health and to serve as role models for RNs in direct patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 38 publications
1
57
1
3
Order By: Relevance
“…Nurses in a qualitative study stated that irregular rotating shift work made it di cult to participate in a healthy lifestyle behavior because they had to spend time in recovering from such irregular rotation working schedule. As a result, they had less time or energy to hang out with family/friends or to participate to exercise schedule or other stress reduction behaviors [25,26]. In terms of monthly income per person, we found that nurses with higher income, they got higher score in all subscales and overall HPLP.…”
Section: Discussionmentioning
confidence: 78%
“…Nurses in a qualitative study stated that irregular rotating shift work made it di cult to participate in a healthy lifestyle behavior because they had to spend time in recovering from such irregular rotation working schedule. As a result, they had less time or energy to hang out with family/friends or to participate to exercise schedule or other stress reduction behaviors [25,26]. In terms of monthly income per person, we found that nurses with higher income, they got higher score in all subscales and overall HPLP.…”
Section: Discussionmentioning
confidence: 78%
“…A culture of selfsacrifice may contribute to the high rates of physical and emotional exhaustion within the nursing profession and may be at the root of compromised self-care among nurses (Mellor et al, 2017). This, in turn, may culminate in burnout and a desire to leave nursing for a less stressful career (Friganovic et al, 2017;Ross et al, 2018).…”
Section: Background and Purposementioning
confidence: 99%
“…Given the shift in health-care focus to health promotion as the fiscally optimal approach, it is critical to extend this to promoting the wellness of the health-care workers themselves. While nurses have knowledge of the benefits of healthpromoting behaviors, they do not employ these in their own self-care practices (Ross et al, 2018). Nurses are expected to advocate health-promoting behavior for their patients, while simultaneously being expected to "do without" or sacrifice their personal needs, making self-sacrifice an integral part of the profession.…”
Section: Background and Purposementioning
confidence: 99%
“…Peplonska et al (2015) connected obesity in midwives with repetitive night-shift duty (8 or more nights per month), BMI being over 30 kg/m 2 . Whether being overweight is specific to midwifery or is part of the general trend has been answered by Ross et al (2019). In a recent paper they reported that more than half of their nursing sample was either overweight or obese.…”
Section: Introductionmentioning
confidence: 99%